Comparison of Effectiveness of Presenting Images in Visual Education of Students on Brain Function - Neda Javadi; Mahdieh Rahmanian; Ahmad Alipour (Zanjan University of Medical Sciences and Health Services, 2019)
Background & Aim: Instead of being based on reality, theoretical approaches related to the occurrence of learning are more based on the observations by researchers. One of the approaches is the study of the effect of changes in virtual education based on the physiological approach. This study aimed to compare the effectiveness of presentation of images in visual education on the brain function of students. Materials and Methods: This study had a 2x2x2 factorial experiment design to compare the effects of three independent variables of spatial intelligence (low and high), depth (2D and 3D), and motion (statistic, dynamic) on two dependent variables of alpha power and recall. Statistical population included all students of Baqiyatallah University of Medical Sciences, Tehran, Iran, who were selected by purposive sampling and were randomly divided into two test groups. The mental rotation test by Vandenberg and Kuse was applied to classify the two groups into high and low spatial intelligence groups while a research-made test and an electroencephalogram were exploited to measure recall and record brain waves, respectively. Results: According to the results of the analysis of variance, no significant difference was observed among visual educational styles in terms of the range of alpha. However, the interaction effects of spatial intelligence and motion on the power of alpha waves were significant. Conclusion: According to the results of the study, the mean scores of the alpha wave was lower in the group of high spatial intelligence, compared to the other group, during a teaching by static images. Through education with animated images, the alpha waves were higher in the subjects with high spatial intelligence, compared to the other participants. It could be concluded that 2D animated images and 3D animated imaged were more effective for individuals with low and high spatial intelligence, respectively.